Shining Bright at 960 nm: A 28‐Silver‐Atom Nanorod Stabilized by DNA - Giacomo Romolini; Hiroki Kanazawa; Christian Brinch Mollerup; Mikkel Baldtzer Liisberg; Simon Wentzel Lind; Zhiyu Huang; Cecilia Cerretani; Jiro Kondo; Tom Vosch (Small Structures)
Fluorescence imaging is a key tool in biological and medical sciences. Despite the potential for increased imaging depth in the near‐infrared range, the limited availability of bright emitters hinders its widespread implementation. In this work, a DNA‐stabilized silver nanocluster (DNA–AgNC) with bright emission at 960 nm in solution is presented, which redshifts further to 1055 nm in the solid and crystalline states. The atomic structure, composition and charge of this DNA–AgNC are determined by combining single‐crystal X‐ray diffraction and electrospray ionization–mass spectrometry. This unique atomically precise silver nanocluster consists of 28 silver atoms, of which are neutral (Ag28 16+), arranged in a rodlike shape, and measures just over 2 nm in length. Interestingly, differences are observed in the number of chlorido ligands between the solution and crystalline states, highlighting the important but not yet fully understood role of chlorides in fine‐tuning the optical properties of this class of emitters. The structure of this silver nanorod, along with the fully characterized photophysical properties, represents a cornerstone for understanding the intricate interactions between silver and DNA bases, as well as paving the way for the rational design of the next‐generation imaging probes.